تحليل نقاط القوة والضعف لتقارير تقييم الأثر البيئي في الساحل السوري - جناد, هيثم; أحمد, فوندا (Latakia University Journal -Engineering Sciences Series, 2014)
يعدّ إعداد تقارير تقييم الأثر البيئي(EIA) بجودة عالية أحد العناصر الهامة في ترجمة فعالة لممارسة هذه العملية. هدف هذا البحث إلى تقييم جودة مجموعة من تقارير تقييم الأثر البيئي العائدة لقطاعات تنمية مختلفة والمعدة في الساحل السوري باستخدام حزمة (Lee at all 1999 )"Cooley & Lee" بالإضافة الى إجراء استبيان مع خبراء تقييم الأثر البيئي في المنطقة الساحلية لمعرفة آرائهم حول جودة التقارير المنفذة وصعوبات العمل وأخذ آرائهم حول التشريعات المتبعة في سوريا. كشف البحث عن وجود عدة نقاط ضعف وأوجه قصور في بعض المجالات المتعلقة بإعداد التقارير, وعن الحاجة لإصدار توجيهات خاصة بالمنطقة الساحلية من شأنها تطوير هذه العملية , وفي النهاية قدمت الدراسة الاقتراحات والتوصيات التي من شأنها تحسين عملية تقييم الأثر البيئي بشكل عام. The preparation of the environmental impact assessment report (EIA) with high quality is one of the important elements in the effective translation of this practice into this process. The objective of this research is to assess the quality of a set of EIA reports belonging to different development sectors on the Syrian coast using the package "Cooley & Lee" (Lee at all 1999), in addition to conducting a questionnaire of the environmental impact assessment in the coastal area with some experts to find out their views on the quality of the reports executed and the difficulties of working, and taking their views on the legislation adopted in Syria. This research reveals the existence of several weaknesses and shortcomings for the preparation of reports in some areas, and the need for guidance especially in the coastal area which will develop this process. Finally, we provide suggestions and recommendations that will improve the environmental impact assessment process in general.